Bridging the gap: from simulation to clinical practice. (April 2014) - Irvine, Susan; Martin, Jenepher
Summary Background There has been a shift from the initial learning of skills on patients in the clinical setting to initial learning in a simulated environment, using part‐task models, with the risk of a task focus to the learning. We contend that quality learning in both the simulated and the clinical environment is crucial to enhance the transferability of skills to the clinical setting. Context We describe teaching strategies, with the sequencing of events and increasing complexity, for the simulated training of basic procedural skills. These teaching strategies can be readily implemented into basic skills training to 'bridge' the gap between the simulated environment and the clinical setting. Implications We suggest that our approach takes basic skills training beyond a task‐focused approach to exemplify clinical scenarios encountered in real life. We argue that there is a need to broaden the focus of medical student training in basic procedural skills, and that the use of a preceptor model of supervision in the clinical setting better enables the transferability of the skills. Although our strategies are based on learning theory, well‐designed research is required to test the efficacy in improving medical student learning.